French Technological Thought and the Nonhuman Turn - Chalmers, Madeleine (Crosscurrents : CROSS, 2024)
iFrench Technological Thought and the Nonhuman Turn/i traces a genealogy of thinking and writing about technology, which takes us from the French avant-gardes to the contemporary ‘nonhuman turn’ in Anglo-American theory via the Surrealists, Gilbert Simondon, and Gilles Deleuze. Tracking the unruly transition from Catholic vocabularies of grace, potentiality, and actuality to the modern and contemporary secular lexicon of agency, virtuality, and affect, this book explores technology as a source of subject matter and conceptual metaphors, but also probes how ideas and words are modes of technicity through which we shape and reshape the world. Fusing literature, philosophy, and theology, it offers readers new contexts – and questions – for the egalitarian ontological commitments of contemporary post- and nonhuman thinking.